Implementing risk management on software intensive projects - Conrow, E.H.; Shishido, P.S. (IEEE software, 1997)
Rising costs, falling performance, and slipping schedules are common problems on large scale software projects. The authors describe key risk issues and how they were mitigated in one DoD (military) project.